An Impossibility Theorem for Gerrymandering. Issue 10 (26th November 2018) - Alexeev, Boris; Mixon, Dustin G.
Abstract: In 2018, the U.S. Supreme Court considered a proposed mathematical formula to help detect unconstitutional partisan gerrymandering. We show that in some cases, this formula only flags bizarrely-shaped districts as potentially constitutional.